Analisis Penggunaan Bahan Bakar Etanol-Pertalite Pada Motor Honda Scoopy 110 cc - Mohamad Rifal; Wawan Rauf (Universitas Gorontalo, 2018)
The production of the crude oil in Indonesia is slowly deceasing by the year, while the consumption of the fuel is still increasing. The matter being comparable within its consumtion is that it makes Indonesia keep impoerting the fuel in order to fulfill its need in every year. It is because there is no new invention of the new oil-mill. Thus, a new penetration to provide an alternative fuel to press the consumption level is needed. Ethanol however, is one of the newest alternative fuels which can be used as the additional substance of the use of the fossil fuel. Ethanol contains of up to 35% oxygen so that it will produce the perfect combustion even if it is in small unit of substance. The aim of this research was to find out the effect of the use of the mixture of the ethanol-pertalite toward the fuel combustion. The research was using the Honda Scoopy 110 cc motorcycle with 1 cylinder injection system. The liquid tank is designed by using plastic container so that it will be possible to be detached and paired to make the consumtion measuring easier. The test vehicle was operated above chasis dynamometer. Engine scanner, especially for Honda was used to sett the rpm, finding out the throotle position, ignition timing, oxygen sensor and the ratio of water fuel. The result of the research was showing that the use of the mixture fuel E-40 is the best mixture, in which E-40 usage is 14,3% more frugal rather that the combustion of the pure pertalite.